MODELLING OF PREVOCATIONAL EDUCATION OF STUDENTS WITH SPECIAL EDUCATIONAL NEEDS: SITUATION AND OPPORTUNITIES - Baranauskienė, Ingrida; Valaikienė, Aistė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of the present article – to reveal the directions of prevocational education of students with SEN, actual situation and opportunities. In 2012 in Lithuania the research of the Delphi group was performed where 13 experts having direct pedagogical experience in working with students having SEN participated. In the article the influence of traditions in the country on the success of prevocational education, the importance of the creation of the interaction child-family-school-community have been analyzed, the main aims of prevocational education, actual situation and directions to be improved have been revealed.